Pengaruh Resilience At Work terhadap Work Life Balance pada Guru SMA - Muhammad Husni Muizz; Dinda Dwarawati (UNISBA Press, 2022)
Abstract. This study aims to determine the effect of resilience at work on work-life balance in high school teachers in Bandung with 159 teachers as a subject. The research method used is the causality method with quantitative design. The measuring instrument used in this research is the resilience at work measuring instrument from Malik and Garg (1) and work-life balance scale from Fisher's measuring instrument adapted by Gunawan (2). The sampling technique in this study used the quota sampling technique. The analytical technique used is Structural Equation Modeling (SEM). The results showed that 88% of high school teachers in Bandung City had a high level of resilience at work and 89% of high school teachers had a high work-life balance. The results of the hypothesis test state that workplace resilience has a positive and significant effect on work life balance of 42%. Then the results resilience at work's dimension on work-life balance had states that the dimensions have the largest to the smallest influence are managing stress 0.245, building social relationships 0.204, staying healthy 0.186, for your calling 0.166, maintaining perspective 0.161, and living, authentic 0.127. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh resilience at work terhadap work life balance pada guru SMA di Kota Bandung dengan jumlah subjek 159 guru. Metode penelitian yang digunakan adalah metode kausalitas dengan desain kuantitatif. Alat ukur yang digunakan dalam penelitian ini adalah alat ukur resilience at work dari Malik dan Garg (1) yang diadaptasi oleh peneliti dan alat ukur Fisher yang diadaptasi oleh Gunawan (2). Teknik sampling pada penelitian ini menggunakan teknik quota sampling. Teknik analisis yang digunakan adalah Structural Equation Modelling (SEM). Hasil penelitian menunjukkan bahwa 88% guru SMA di Kota Bandung memiliki tingkat resilience at work yang tinggi dan 89% guru SMA memiliki tingkat work life balance yang tinggi. Hasil uji hipotesis menyatakan bahwa resilience at work berpengaruh positif dan signifikan terhadap work life balance sebesar 42%. Kemudian hasil uji setiap dimensi resilience at wor terhadap work life balance menyatakan bahwa semua dimensi memiliki nilai positif dan berpengaruh secara signifikan. Dengan dimensi yang memiliki pengaruh paling besar hingga paling kecil adalah managing stress 0,245, building social connection 0,204, staying healthy 0,186, for your calling 0,166, maintaining perspective 0,161, dan living, authentically 0,127.